Enzyme Replacement Therapy and Hematopoietic Stem Cell Transplantation Results in Patients with Hurler Syndrome: Clinical Cases - Nato D. Vashakmadze; Leyla S. Namazova-Baranova; Natalia V. Zhurkova; Ekaterina Yu. Zakharova; Svetlana V. Mikhaylova; Grigory V. Revunenkov ("Paediatrician" Publishers LLC, 2019)
Mucopolysaccharidosis type I (MPS I) is the hereditary disease characterized with alpha-L-iduronidase activity decrease and further accumulation of heparan and dermatan sulfate in lysosomes. MPS I is rare autosomal recessive disorder with incidence of 0.5-4 cases on 100.000 live-birth infants. Meantime there two approaches in MPS I treatment: hematopoietic stem cell transplantation (HSCT) and enzyme replacement therapy (ERT). HSCT can be the best option for treatment of patients with severe MPS I (Hurler syndrome). Successful engraftment moderates such clinical signs as obstructive airway diseases, hepatosplenomegaly, cardiovascular system dysfunctions. HSCT prevents cognitive functions decline and other pathologic features of central nervous system. Presented clinical cases show various clinical courses according to age of diagnosis, ERT onset and HSCT implementation.